2009
DOI: 10.1097/hjh.0b013e32832531e6
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension alters the function of nitrergic and sensory innervation in mesenteric arteries from female rats

Abstract: In contrast to male rats, electrical field stimulation-induced contractions are decreased in hypertensive female rats. Nitrergic innervation plays a role in the development and/or maintenance of hypertension, whereas sensory innervation is a counteracting mechanism through the increased calcitonin gene-related peptide response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…However, we have observed that sensory innervation might increase its participation in several pathological conditions such as hypertension and diabetes [28,29]. Indeed, the participation of peptidergic innervation was not observed in any of the experimental groups when CGRP was used, suggesting that HgCl 2 treatment did not affect this innervation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…However, we have observed that sensory innervation might increase its participation in several pathological conditions such as hypertension and diabetes [28,29]. Indeed, the participation of peptidergic innervation was not observed in any of the experimental groups when CGRP was used, suggesting that HgCl 2 treatment did not affect this innervation.…”
Section: Discussionmentioning
confidence: 79%
“…We have reported previously that rat mesenteric arteries possess adrenergic, nitrergic and sensory innervation, whose role may change depending on the pathophysiological situation [28][29][30]. EFS (electrical field stimulation) produces a vasoconstrictor response, which is the integrated result of neurotransmitter release, mainly of NA (noradrenaline), NO and CGRP (calcitonin gene-related peptide) [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…In certain experimental conditions, such as hyperaldosteronism and hypertension, alterations in sensory function play a key role in the regulation of mesenteric vascular tone (Balfagón et al, 2004;del Campo et al, 2009). Exogenous CGRP produced a mild vasodilatory response, which was comparable in the three groups.…”
Section: Figurementioning
confidence: 82%
“…NO release was measured as previously described (del Campo et al, 2009). Endothelium-denuded segments from control, HFD and HFD + rosuvastatin rats were subjected to a resting tension of 0.5 g as indicated for reactivity experiments.…”
Section: Release Of Nomentioning
confidence: 99%
“…We have previously reported that in this strain sensory innervation does not participate in vasomotor response induced by EFS in control animals, but that the participation of this innervation is increased in several pathological conditions such as hypertension, cirrhosis and diabetes [12,15,40,41]. In the present study, we observed that pre-incubation with the CGRP antagonist CGRP-(8-37) did not modify the vasoconstrictor response to EFS in mesenteric rings from SO rats, confirming CGRP non-participation in vasoconstriction in healthy Wistar rats [10,36,42].…”
Section: Short-term Phmentioning
confidence: 98%